2020
DOI: 10.1002/mnfr.201900580
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber from Oat and Rye Brans Ameliorate Western Diet–Induced Body Weight Gain and Hepatic Inflammation by the Modulation of Short‐Chain Fatty Acids, Bile Acids, and Tryptophan Metabolism

Abstract: Scope: Dietary fiber (DF) induces changes in gut microbiota function and thus modulates the gut environment. How this modulation is associated with metabolic pathways related to the gut is largely unclear. This study aims to investigate differences in metabolites produced by the gut microbiota and their interactions with host metabolism in response to supplementation with two bran fibers. Methods and Results: Male C57BL/6N mice are fed a western diet (WD) for 17 weeks. Two groups of mice received a diet enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 61 publications
(91 reference statements)
3
43
0
1
Order By: Relevance
“…were generally unaffected, where only Clostridium leptum was significantly reduced. [21] The diminished production partially resulted in the reduced SCFA contents in the liver. The reduction of acetate in the liver could also be attributed to hepatosteatosis, since HFD is known to activate lipogenic genes in the liver, and hence to deploy acetate for de novo lipogenesis (DNL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were generally unaffected, where only Clostridium leptum was significantly reduced. [21] The diminished production partially resulted in the reduced SCFA contents in the liver. The reduction of acetate in the liver could also be attributed to hepatosteatosis, since HFD is known to activate lipogenic genes in the liver, and hence to deploy acetate for de novo lipogenesis (DNL).…”
Section: Discussionmentioning
confidence: 99%
“…[24] This was also evidenced by the fecal bacterial profile showing elevated Lactobacilli but not Bacteroides and Bifidobacterium in the OAT group. [21] It additionally explains the lack of synergistic effects of LGG and OAT in the cecum content, since oat beta-glucan could have promoted the growth of LGG, which outcompete the acetate-producing bacteria for the prebiotic resources. Nevertheless, LGG and OAT synergistically increased acetate and propionate in the liver, suggesting that they regulated metabolic homeostasis of SCFA although their rates of production in the cecum were not restored.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the administration of isomaltodextrin was positively related to the concentrations of acetic and butyric acids in mice with glucometabolic disorder [ 38 ]. Moreover, an in vivo study revealed that the intervention of dietary fiber from oat and rye brans improved body weight, glucose metabolism, hepatic inflammation, and SCFAs production in mice, accompanied with regulating bile acids and tryptophan-serotonin metabolism [ 77 ]. Furthermore, the amylosucrase-modified chestnut starch could ameliorate obesity in mice by upregulating the SCFAs-GPR43-mediated signaling pathway [ 23 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%
“…A principal mechanism that the intestinal microbiome affects remote organs is through the metabolism of SCFA’s [ 25 , 26 ]. Soluble dietary fiber can produce large quantities of SCFA’s which then participate in the progression of inflammation and allergic diseases.…”
Section: Discussionmentioning
confidence: 99%